Antimicrobial Efficacy of Indolicidin Against Multi-Drug Resistant Enteroaggregative Escherichia coli in a Galleria mellonella Model - Vergis, Jess; Malik, Satyaveer Singh; Pathak, Richa; Kumar, Manesh; Ramanjaneya, Sunitha; Kurkure, Nitin Vasantrao; Barbuddhe, Sukhadeo Baliram; Rawool, Deepak Bhiwa (Frontiers in Microbiology, 2019)
Antimicrobial resistance against Enteroaggregative Escherichia coli (EAEC), an emerging food-borne pathogen, has been observed in an increasing trend recently. In the recent wake of antimicrobial resistance, alternate strategies especially, cationic antimicrobial peptides (AMPs) have attracted considerable attention to source antimicrobial technology solutions. This study evaluated the in vitro antimicrobial efficacy of indolicidin against multi-drug resistant enteroaggregative Escherichia coli (MDR-EAEC) strains and further to assess its in vivo antimicrobial efficacy in Galleria mellonella larval model. The minimum inhibition concentration (MIC; 32 µM) and minimum bactericidal concentration (MBC; 64 µM) of indolicidin against MDR-EAEC was determined by micro broth dilution method. Indolicidin was also tested for its stability (high-end temperatures, physiological concentration of salts and proteases); safety (sheep RBCs; HEp-2 and RAW 264.7 cell lines); effect on beneficial microflora (Lactobacillus rhamnosus and L. acidophilus) and its mode of action (flow cytometry; nitrocefin and ONPG uptake). In vitro time-kill kinetic assay of MDR-EAEC treated with indolicidin was performed. Further, survival rate, MDR-EAEC count, melanisation rate, hemocyte enumeration, cytotoxicity assay and histopathological examination were carried out in G. mellonella model to assess in vivo antimicrobial efficacy of indolicidin against MDR-EAEC strains. Indolicidin was tested stable at high temperatures (70℃; 90℃), physiological concentration of cationic salts (NaCl; MgCl2) and proteases, except for trypsin and tested safe with sheep RBCs and cell lines (RAW 264.7; HEp-2) at MIC (1X and 2X); the beneficial flora was not inhibited. Indolicidin exhibited outer membrane permeabilisation in a concentration- and time-dependent manner. In vitro time-kill assay revealed concentration-cum-time dependent clearance of MDR-EAEC in Indolicidin-treated groups at 120 min, while, in G. mellonella, the infected group treated with Indolicidin revealed an increased survival rate, immunomodulatory effect, reduced MDR-EAEC counts and were tested safe to the larval cells which was concurred histopathologically. To conclude, the results suggests indolicidin as an effective antimicrobial candidate against MDR-EAEC and we recommend its further investigation in appropriate animal models (mice/piglets) before its application in the target host.